2018
DOI: 10.4324/9781351026987
|View full text |Cite
|
Sign up to set email alerts
|

Young People, Social Media and Health

Abstract: The pervasiveness of social media in young people's lives is widely acknowledged, yet there is little evidence-based understanding of the impacts of social media on young people's health and wellbeing. Young People, Social Media and Health draws on novel research to understand, explain, and illustrate young people's experiences of engagement with health-related social media; as well as the impacts they report on their health, wellbeing, and physical activity. Using empirical case studies, digital representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Among groups of social media users, teenagers and youths are the most vulnerable age group; although they are the youngest, teenagers are also the ones who spend the most time online and thereby becoming the ones most exposed to the underlying risks of social media [ 11 ]. Common impacts of social media overuse on young people included sleep disruption, reduced attention span, negative self-perception, and cyberbullying [ 12 , 13 ]. While there has been substantial evidence on the use of social media from a health viewpoint, a review of the literature showed that less than 10 studies focused on teenagers and included adolescents in their sample [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among groups of social media users, teenagers and youths are the most vulnerable age group; although they are the youngest, teenagers are also the ones who spend the most time online and thereby becoming the ones most exposed to the underlying risks of social media [ 11 ]. Common impacts of social media overuse on young people included sleep disruption, reduced attention span, negative self-perception, and cyberbullying [ 12 , 13 ]. While there has been substantial evidence on the use of social media from a health viewpoint, a review of the literature showed that less than 10 studies focused on teenagers and included adolescents in their sample [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neumark-Sztainer et al, 2006). Conversely, such comparisons are also important for motivation and helping young people to navigate their social worlds (Goodyear and Armour, 2019). Consequently, this context of peer comparison in adolescence points to important areas for research concerned with the unique affordances of technological tools for this population.…”
Section: Social Pressuresmentioning
confidence: 99%
“…Recently, research has also started to explore the influence of SMU on eating‐related thoughts, feelings and behaviours. As such, strong correlations between SMU and disordered eating traits have been observed in young adults 10 and, specifically, increased time spent on Instagram and Snapchat has been strongly associated with increased disordered eating behaviours 11 . Thus, with 90% of 18–29 year olds being active on SM, the majority of young adults may be exposed to this potential risk 12 …”
Section: Introductionmentioning
confidence: 99%